2010
DOI: 10.1128/jvi.01006-10
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Drug Repositioning for Discovery of a Novel HIV Combination Therapy

Abstract: The development of HIV drugs is an expensive and a lengthy process. In this study, we used drug repositioning, a process whereby a drug approved to treat one condition is used to treat a different condition, to identify clinically approved drugs that have anti-HIV activity. The data presented here show that a combination of two clinically approved drugs, decitabine and gemcitabine, reduced HIV infectivity by 73% at concentrations that had minimal antiviral activity when used individually. Decreased infectivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
94
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(97 citation statements)
references
References 39 publications
3
94
0
Order By: Relevance
“…Lori et al, in 2005 [13] showed that a cytostatic 10 µM concentration of HU inhibited cell proliferation and suppressed HIV-1 replication in vitro. In a virostatic combination with didanosine, the indirect antiviral effect of HU and the direct antiviral effect of didanosine resulted in an overall beneficial effect [13,19,20,23,24]. On its own, compound 4 exhibited antiviral activity (lowering infectivity of TZM-bl cells by Du…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Lori et al, in 2005 [13] showed that a cytostatic 10 µM concentration of HU inhibited cell proliferation and suppressed HIV-1 replication in vitro. In a virostatic combination with didanosine, the indirect antiviral effect of HU and the direct antiviral effect of didanosine resulted in an overall beneficial effect [13,19,20,23,24]. On its own, compound 4 exhibited antiviral activity (lowering infectivity of TZM-bl cells by Du…”
Section: Figmentioning
confidence: 99%
“…The HU-didanosine combination decreases deoxyribonucleotides (dNTPs) resulting in an increase in the dNTP analogue (didanosine) which is a nucleotide reverse transcriptase inhibitor resulting in an increase in anti-HIV activity [21,22]. The combination of cytostatic drugs with anti-viral agents, results in an overall significantly beneficial anti-HIV effect [13,19,20,23,24]. Lori and colleagues [13,19] named this combination virostatics and defined it as a class of emerging anti-HIV agents which are characterised by the combination of a drug directly inhibiting virus production (viro) e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Mammalian innate immune systems have developed a mechanism to exploit this high mutation rate against the virus; in a phenomenon termed "lethal mutagenesis," (6)(7)(8)(9)(10)(11)(12)(13)(14) the immune system employs nucleic acid-modifying enzymes (e.g., APOBEC and ADAR) to increase the viral mutation rate sharply, stressing the functional gene product repertoire of the virus to the point that the viral population collapses (15)(16)(17). Several antiviral agents are proposed to work at least in part by a chemical version of lethal mutagenesis [e.g., ribavirin against hepatitis C virus (18-22), 5-hydroxy-2′-deoxycytidine against HIV (7), and T-705 against influenza viruses (23)].…”
mentioning
confidence: 99%
“…The main advantage is that host-acting BSAs can cover multiple viruses and genotypes while reducing at the same time the likelihood of resistance development 69,70 . In the clinical setting, applications of BSAs might range from rapid management of new or DAA-resistant viral strains 71 and of viral outbreaks 12 to reducing therapy complexity of viral co-infections [72][73][74][75] . In addition, BSAs would be ideal as a first-line treatment or the prophylaxis of acute virus infections such as respiratory tract or sexually transmitted infections 76,77 .…”
Section: Pros and Cons Of Broad-spectrum Antivirals (Bsas)mentioning
confidence: 99%